KREDIBILITAS MEDIA SOSIAL INSTAGRAM @SEMUATENTANGBATAM PADA PEMENUHAN INFORMASI FOLLOWERS - yuliatin, yuliatin; abidin, sholihul (SCIENTIA JOURNAL, 2021)
@semuatentangbatam is an Instagram social media account that contains information about Batam City. This account make it easier for the public to find information about what is happening in Batam City. The author is interested in knowing the credibility of @semuatentangbatam social media account in terms of following Followers information. The research was classified as a quantitative descriptive. The sampling technique of this research was Isaac and Michael with 348 respondents of sample value. The research data were collected from questionnaire and the method that used is share link of the questionnaire to @semuatentangbatam followers.The research found that: a) The results of the data validity test, the data that has been tested on the x and y variables is declared valid. b) The results of the data reliability test using Conbrach's Alpha the value obtained is 0.844 for the credibility variable and the value is 0.874 for the results of the information fulfillment variable, it can be concluded that each variable is considered reliable. c). The results of the normality test, each variable is normally distributed. d) It is known that the credibility variable has a positive and significant effect on the information fulfillment variable. The results of several tests carried out on the x variable against the y variable show that the hypothesis in this study is that the credibility of Instagram social media has an influence on its followers to meet the information they need. Keywords: Credibility, fulfillment of information, instagram